2000
DOI: 10.1088/0031-9120/35/2/311
|View full text |Cite
|
Sign up to set email alerts
|

Facts and feelings: exploring the affective domain in the learning of physics

Abstract: This article presents the results of a comparative study of two groups of learners. The study explores whether their feelings about a potentially emotive topic-radioactivity in this caseinfluence their approach to learning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
5

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 7 publications
1
17
0
5
Order By: Relevance
“…These included irradiation confused with contamination, radiation inducing radioactivity in the exposed material, and believing that gamma radiation is the best at penetrating, simply because it is the most energetic. These findings are unique to this study although the last finding has also been reported by Alsop and Watts (2000a) for 16 to 19 year olds studying physics in schools in the |UK.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…These included irradiation confused with contamination, radiation inducing radioactivity in the exposed material, and believing that gamma radiation is the best at penetrating, simply because it is the most energetic. These findings are unique to this study although the last finding has also been reported by Alsop and Watts (2000a) for 16 to 19 year olds studying physics in schools in the |UK.…”
Section: Discussionsupporting
confidence: 62%
“…This affective aspect of radioactivity and ionising radiation appears to have been less rigorously researched than the cognitive. Alsop and Watts (2000a) reported that 16-19 year olds studying physics in schools in the UK gave more rational and less emotive responses than non-science undergraduates, although the differences were not clear-cut. They concluded that studying physics beyond the years of compulsory schooling helps students 'arrive at equilibrium between their wariness of the issues and an informed view of the matters involved ' (p. 138).…”
Section: Introductionmentioning
confidence: 99%
“…Because it is clearly understood that one cannot achieve the intended success unless he stops ignoring the affective features of the students (Seah and Bishop, 2000;Dede and Yaman, 2008;Yenice, Saydam and Telli, 2012). In many of the studies in this field, affective domain skills have also been claimed to have a positive effect on students' achievements (Alsop and Watts, 2000;Chen, 2001., Duit andTreagust, 2003;Cengiz, 2009;Yenice, Saydam and Telli, 2012).…”
mentioning
confidence: 99%
“…Alsop and Watts [55] suggest that students' attitudes towards learning topics such as radioactivity is influenced by their emotions towards the effects of radiation on living beings. They argue that our aim should be towards instruction that balances the learning of physics ideas with emotional wariness towards such topics, but they do not investigate how such balance might occur in an actual learning situation, or how the emotions they document become consequential when students are actually learning about the topic.…”
Section: B Learners Conceptual and Epistemological Reasoning Might Bmentioning
confidence: 99%